Concept of Time Travel and The Different Theories for Making It Possible and The Implications of Time Travelling - Younus, Muhammad; Nurmandi, Achmad; Suswanta, Suswanta (Riviera Publishing, 2023)
The purpose of this paper is to explain in detail the concept of time travel, also how it was popularized, and lastly, the theories presented to make it possible and what impact it will have if time travel becomes possible soon. This research uses qualitative research type, evaluating data from qualitative research is